The impact of different commercial probiotic cultures with starters on technological, physicochemical and sensorial properties of a traditional yogurt-based appetizer "Cacık" - Altuntas, Seda (Array, 2019)
The selection of proper probiotic culture is essential for maintaining adequate numbers of viable cells until consumption since potential adverse interaction between selected strain and starter culture. This study examined the suitability of Cacık as a potential probiotic carrier including Lactobacillus acidophilus 74-2, Lactobacillus rhamnosus Howaru HN001TM and Bifidobacterium longum BB536 in different combinations. The presence of three probiotic strains caused higher post acidification and shorter fermentation time associated to higher counts of L. bulgaricus. Except for certain combinations containing B. longum BB536, the counts of individual probiotic bacteria were higher than 6 log g-1 for all probiotic supplemented Cacık samples. Results showed that bacterial interaction was decisive for survival over 21 days of storage. Probiotic products containing only B. longum BB536 or B. longum BB536 with L. acidophilus 74-2 did not accomplish in terms of the technological point, since the viable cell counts decerased for 2.45 log and 1.95 log per g, respecitevly, throughout the storage period. In three of totally four combinations included L. rhamnosus Howaru HN001TM alone or combined with other probiotic bacteria, the viable cell counts of L. rhamnosus Howaru HN001TM remained at the inoculated level, while the counts significantly increased in co-culture with L. acidophilus 74-2. Considering the overall sensorial attributes and survival of probiotics, Cacık supplemented with L. rhamnosus Howaru HN001TM alone, combinations of B. longum BB536 and L. rhamnosus Howaru HN001TM or L. acidophilus 74-2 and L. rhamnosus Howaru HN001TM or by all of the three tested probiotics, were suggested as suitable for further production.